2012
DOI: 10.1007/s00394-012-0331-7
|View full text |Cite
|
Sign up to set email alerts
|

Does equol production determine soy endocrine effects?

Abstract: Isoflavones, a group of phytoestrogens, are selective oestrogen receptor (ER) modulators. They may positively impact endocrine-related conditions but the current evidence is sparse. Equol, a non-steroidal oestrogen, is produced by the metabolism of the isoflavone daidzein by intestinal bacteria. In Western countries, 30-50% of individuals metabolize daidzein into equol and are known as equol producers. Equol production may be the source of benefit from isoflavones in endocrine disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 133 publications
2
51
1
Order By: Relevance
“…Estrogens with intermediate strength supported MCF-7 cell proliferation at 1-100 nM and included two representative industrial chemicals BPA and p-nonylphenol (PNP) (1,19). The isoflavone phytoestrogens genistein and daidzein, which require metabolic activation for their full-strength estrogenic actions (20), were weak estrogens that supported MCF-7 cell proliferation at 0.1-10 μM. Based on these results, we selected estrogen concentrations for which the seed transcriptomal profiles were determined (indicated in Fig.…”
Section: Generation Of Computational Models Of Dose-dependent Transcrmentioning
confidence: 99%
“…Estrogens with intermediate strength supported MCF-7 cell proliferation at 1-100 nM and included two representative industrial chemicals BPA and p-nonylphenol (PNP) (1,19). The isoflavone phytoestrogens genistein and daidzein, which require metabolic activation for their full-strength estrogenic actions (20), were weak estrogens that supported MCF-7 cell proliferation at 0.1-10 μM. Based on these results, we selected estrogen concentrations for which the seed transcriptomal profiles were determined (indicated in Fig.…”
Section: Generation Of Computational Models Of Dose-dependent Transcrmentioning
confidence: 99%
“…Equol is a metabolite produced in the gastrointestinal tract by bacterial metabolism of daidzein, and there is some evidence that equol has higher hormonal activity that genistein and daidzein 30, 3130, 32 but its role in humans remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and animal studies have shown that equol has anti‐androgenic and anti‐proliferative properties in the prostate,30, 32 but its role in humans remains unclear. Equol production varies between individuals, and the term equol‐producers refers to people who produce equol after consuming isoflavones; therefore it may be possible that the health benefits of soya‐based diets are greater in equol‐producers than in equol non‐producers 33…”
Section: Discussionmentioning
confidence: 99%
“…Diet may change the bacterial population and then affect equol production 20. Asian soy‐rich dietary habits are considered to work in favor of equol production.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of equol producers is higher in vegetarians18 and Asian populations and is considered to be associated with the amount of soy intake 19. Equol is more bioavailable than other soy isoflavones, and equol producers are believed to benefit more from soy isoflavones 20. It is plausible that isoflavones may stabilize hormonal fluctuations of the estrogen cycle through their SERM‐like properties and then alleviate premenstrual symptoms 21.…”
Section: Introductionmentioning
confidence: 99%